A Comparison among Score Systems for Discharging Patients from Recovery Rooms: A Narrative Review - Khadija El Aoufy; Carolina Forciniti; Yari Longobucco; Alberto Lucchini; Ilaria Mangli; Camilla Elena Magi; Enrico Bulleri; Cristian Fusi; Paolo Iovino; Pasquale Iozzo; Nicoletta Rizzato; Laura Rasero; et al. (Nursing Reports)
Introduction: The recovery room (RR) is a hospital area where patients are monitored in the early postoperative period before being transferred to the surgical ward or other specialized units. The utilization of scores in the RR context facilitates the assignment of patients to the appropriate ward and directs necessary monitoring. Some scoring systems allow nurses to select patients who can be discharged directly to their homes. Aim and methods: The aim of this narrative review was to describe and compare the scoring systems employed to discharge postoperative patients from RR, with a focus on item characteristics. Results: Nine scoring systems were identified and discussed: the “Aldrete Score System” and its modified version, the “Respiration, Energy, Alertness, Circulation, Temperature Score”, the “Post Anesthetic Discharge Scoring System”, the “White and Song Score”, the “Readiness for Discharge Assessment Tool”, the “Anesthesia and Perioperative Medicine Service Checklist”, the “Post-Anesthetic Care Tool”, the “Post-operative Quality Recovery Scale”, and the “Discerning Post Anesthesia Readiness for Transition” instrument. Discussion and conclusions: To obtain a comprehensive overview, the items included in the scoring systems were compared. Despite the availability of guidelines for patients’ discharge readiness from the RR, there is no universally recommended scoring system. Next-generation scores must be improved to ease their use, minimize errors, and increase safety. The main goals of the scores included in this narrative review were to be simple to use, feasible, intuitive, comprehensive, and flexible. However, these goals frequently conflict because patient assessment takes time, and a smart and comprehensive score may not consider some clinical parameters that may be crucial for the discharge decision. Therefore, further research should be conducted on this topic.